Frontiers in Offshore Geotechnics : ISFOG 2005 : proceedings of the first International Symposium on Frontiers in Offshore Geotechnics, University of Western Australia, Perth, 19-21 September 2005 /: ISFOG 2005 : proceedings of the first International Symposium on Frontiers in Offshore Geotechnics, University of Western Australia, Perth, 19-21 September 2005. ([2005]) - Unknown
No abstract available